Kebijakan- Kebijakan Pemerintah Di Masa Pandemi Dalam Perspektif Hukum Kesehatan - Nur Aini Rahmawati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
This study examines government policies during the COVID-19 pandemic in terms of health law. Health law is one of the laws reviewed in the COVID-19 pandemic. In handling the COVID-19 pandemic, the Government has issued several legal products such as Government Regulations that also implement the PSBB and Physical Distancing policies, but these policies are not effective in breaking the chain of COVID-19 spread, as seen the number of COVID-19 cases in Indonesia on January 28, 2021, has reached through 1 million cases, the highest in Southeast Asia. This type of research is a normative juridical research that is descriptive in nature by providing solutions to the handling of COVID-19 in Indonesia. This study concludes that the legal politics taken by the government (PSBB and physical distancing) in handling COVID-19 have not maximally protected the right to health of the Indonesian people as mandated by the constitution Article 28H paragraph (1) and Article 34 paragraph (2) and (3) of the 1945 Constitution. The government should implement a partial lockdown policy as China's success in carrying out a partial lockdown in Wuhan. With a partial lockdown in Jakarta Province as the epicenter of the COVID-19 pandemic in Indonesia, the virus will not spread to other provinces.